HUBUNGAN KETAHANAN MENTAL DENGAN PERFORMA PUNCAK ATLET SEPAKBOLA DI KOTA SEMARANG - Antonius Christian Wibowo; Menik Tetha Agustina (IMAGE, 2023)
This research aims to determine the influence between the mental resilience possessed by athletes and the athletes' peak performance before the competition. The samples that the researchers took were 20 athletes who came from Semarang and were playing at Persik Kendal as well as 20 athletes in the age group under 23 years who competed in a tournament held by ASKOT PSSI Semarang City. This research was conducted using quantitative methods. The sampling technique used was purposive sampling. Data analysis in this research was carried out by means of statistical tests using the SPSS for Windows application version 25.0. Normality test measurements were carried out using the Kolmogorov-Smirov test to determine whether the data was normally distributed or not. The next data test carried out was using the Pearson product moment correlation statistical test to determine the relationship between the two variables, in this case mental endurance and peak performance. Based on the results of research data analysis that has been carried out, it is known that the rx,y value is 0.665 with a significance value of 0.000 (sig > 0.01), thus the hypothesis proposed in this research can be accepted, that there is a very significant positive relationship between mental resilience with peak athlete performance. Keywords : Mental Resilience, Peak Performance, Football Athletes